2010
DOI: 10.1101/lm.1958811
|View full text |Cite
|
Sign up to set email alerts
|

A presynaptic role for FMRP during protein synthesis–dependent long-term plasticity in Aplysia

Abstract: Loss of the Fragile X mental retardation protein (FMRP) is associated with presumed postsynaptic deficits in mouse models of Fragile X syndrome. However, the possible presynaptic roles of FMRP in learning-related plasticity have received little attention. As a result, the mechanisms whereby FMRP influences synaptic function remain poorly understood. To investigate the cellular locus of the effects of FMRP on synaptic plasticity, we cloned the Aplysia homolog of FMRP and find it to be highly expressed in neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 98 publications
(140 reference statements)
0
18
0
1
Order By: Relevance
“…In addition, there is experimental support for a presynaptic role in synapse formation and the establishment of circuitry (Zhang et al 2001b;Hanson and Madison 2007;Bureau et al 2008;Gibson et al 2008). Recent studies on the role of the Aplysia FMRP homolog (ApFMRP) in sensory to motor neuron synaptic plasticity supports both a pre-and postsynaptic role for FMRP in regulating protein synthesis in response to synaptic stimulation (Till et al 2011). A fruitful area for further research is to connect these observations with the set of presynaptic mRNAs whose translation is regulated by FMRP ).…”
Section: Rna-binding Proteins In the Brainmentioning
confidence: 99%
“…In addition, there is experimental support for a presynaptic role in synapse formation and the establishment of circuitry (Zhang et al 2001b;Hanson and Madison 2007;Bureau et al 2008;Gibson et al 2008). Recent studies on the role of the Aplysia FMRP homolog (ApFMRP) in sensory to motor neuron synaptic plasticity supports both a pre-and postsynaptic role for FMRP in regulating protein synthesis in response to synaptic stimulation (Till et al 2011). A fruitful area for further research is to connect these observations with the set of presynaptic mRNAs whose translation is regulated by FMRP ).…”
Section: Rna-binding Proteins In the Brainmentioning
confidence: 99%
“…The local translation of transcripts represents a very important mechanism contributing to synaptic plasticity and arborization (Till et al 2011;Jung et al 2012), axonal growth (Campbell and Holt 2001;Hörnberg and Holt 2013), as well as axonal viability and neuronal development (Taylor et al 2013). In this regard, numerous studies showed that disruption of SMN function causes presynaptic abnormalities and abnormal synaptic transmission with poorly arborized axons at the neuromuscular junction (NMJ) terminals (Jablonka et al 2007;Kariya et al 2008;Kong et al 2009), suggesting that SMN might be directly involved in the regulation of axonal growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, FMRP is also localized to axonal and presynaptic sites in both cultured neurons and the intact brain (Feng et al, 1997a; Antar et al, 2006; Price et al, 2006; Christie et al, 2009; Till et al, 2010; Akins et al, 2012). Several lines of evidence indicate that FMRP has important roles in these axonal and presynaptic domains.…”
Section: Introductionmentioning
confidence: 99%